Disturbance Signal Generation Method of AC Impedance Test Based on Boost Circuit - SHEN Zehua; PENG Zaiwu; CHEN Xiongchun; WANG Jian; LIU Shaochun (Kongzhi Yu Xinxi Jishu)
AC impedance spectrum can comprehensively reflect the parameter information of water, oxygen and hydrogen content of proton exchange membrane fuel cell (PEMFC). In order to realize online monitoring of the health status of the PEMFC of the whole vehicle, this paper presents a AC impedance test disturbance signal generation method for PEMFC based on Boost circuit.It does not need to add additional hardware circuits, uses the main circuit of fuel cell boost DC/DC (multi-phase Boost circuits are connected in parallel), and superimposes AC sine wave disturbance of set frequency and set amplitude on the output DC current in SPWM mode. Based on the input constant current PID control algorithm of the existing DC/DC loop, a corresponding digital controller is constructed, and the physical prototype is tested and analyzed for the generated signal. By analyzing the AC voltage and current fluctuations generated by the disturbance on the DC/DC input side, the AC impedance and phase changes at each frequency point are tested, and the corresponding AC impedance map is drawn. Based on the Randles equivalent circuit of PEMFC and the electrical principle of the fuel cell power system, this paper builds a test bench for simulation test. Through the comparative analysis of the test data, the effectiveness and accuracy of the disturbance signal generation method proposed in this paper are verified.